Media, Business Education and E-Learning: An Insinuative Overview - Hossin , Md. Ekram (American Journal of Trade and Policy, 2016)
Media, education, and e-language are interrelated. Media is the right medium to make profitable business activities. Education enlightens the heart of people and business education can make the people learn about the proper ways of business. So, these three are correlated. Mass media plays a significant role in shaping public perceptions on a variety of important issues in business education. They also function in influencing modern business culture and education by selecting and portraying a particular set of beliefs, values, and traditions as reality. Mass media plays an important role in business education. Business has a noble position as an ideal occupation. Mass media helps to enhance the range of business education for the development of the country as well as the world. This descriptive and analytic research work finds out the insinuative and synchronic synopsis of media, education and e-language. JEL Classifications Code: M19